Alanine aminotransferase-based algorithms of liver stiffness measurement by transient elastography (Fibroscan) for liver fibrosis in chronic hepatitis B - Chan, H. L.-Y.; Wong, G. L.-H.; Choi, P. C.-L.; Chan, A. W.-H.; Chim, A. M.-L.; Yiu, K. K.-L.; Chan, F. K.-L.; Sung, J. J.-Y.; Wong, V. W.-S. (Journal of viral hepatitis, 2009)
The aim of this study is to know the liver stiffness measurement (LSM) cutoffs for different stages of liver fibrosis in chronic hepatitis B (CHB) and to investigate the effect of alanine aminotransferase (ALT) on LSM. We prospectively studied consecutive CHB patients undergoing liver biopsy and transient elastography examinations. Diagnostic performance of LSM for different degrees of liver fibrosis was evaluated. One hundred and sixty‐one CHB patients with adequate liver biopsy sample size were studied. Area under receiver operating characteristics curves of LSM for no fibrosis (F0 vs F1–4), bridging fibrosis (F0–2 vs F3–4) and liver cirrhosis (F0–3 vs F4) was 0.80 (95% CI: 0.68–0.92), 0.87 (95% CI: 0.82–0.93) and 0.93 (95% CI: 0.89–0.97) respectively. For liver cirrhosis, these optimal cutoff values were 8.4 kPa (98% sensitivity), 9.0 kPa (maximum sum of sensitivity and specificity), 13.4 kPa (94% specificity) and 13.4 kPa (maximum diagnostic accuracy, 85%) respectively. Patients with the same fibrosis staging but higher ALT levels tend to have higher LSM, and the diagnostic performance for low stage fibrosis was most seriously affected when ALT was elevated. Different LSM cutoff values and algorithms were derived for normal and elevated ALT levels. Based on these algorithms, liver biopsy can be avoided in 62% and 58% of patients with normal and elevated ALT respectively. In conclusion, transient elastography is a reasonable noninvasive tool to substitute liver biopsy among the lowest and highest risk patients for the assessment of liver fibrosis.